2023
DOI: 10.3390/metabo13070793
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Metabolism In Vivo and In Vitro

Abstract: Red blood cells (RBC) are the most abundant cell in the human body, with a central role in oxygen transport and its delivery to tissues. However, omics technologies recently revealed the unanticipated complexity of the RBC proteome and metabolome, paving the way for a reinterpretation of the mechanisms by which RBC metabolism regulates systems biology beyond oxygen transport. The new data and analytical tools also informed the dissection of the changes that RBCs undergo during refrigerated storage under blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 228 publications
3
57
0
1
Order By: Relevance
“…RBC storage is not only a clinically relevant manipulation of the erythrocyte, but also a form of stress (especially, oxidative stress 12 ) that at least partially recapitulates other biologically-relevant stressors, such as exercise, 39 exposure to drugs (e.g., chemotherapeutic anthracyclines like doxorubicin 40 ), irradiation, or disease (e.g., hemoglobinopathies like sickle cell disease 41 or chronic kidney disease). 3 By leveraging a massive vein-to-vein database, 42 our findings corroborate real-world clinical data generated from decades of studies suggesting a role for ATP levels in the regulation of RBC hemolytic propensity, especially extravascular hemolysis upon transfusion. 43 Similarly, it had been recently reported that hypoxanthine accumulation as a function of adenosine or AMP deaminase activation during storage is a marker of the metabolic storage lesion that predicts extravascular hemolysis in mice and humans.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…RBC storage is not only a clinically relevant manipulation of the erythrocyte, but also a form of stress (especially, oxidative stress 12 ) that at least partially recapitulates other biologically-relevant stressors, such as exercise, 39 exposure to drugs (e.g., chemotherapeutic anthracyclines like doxorubicin 40 ), irradiation, or disease (e.g., hemoglobinopathies like sickle cell disease 41 or chronic kidney disease). 3 By leveraging a massive vein-to-vein database, 42 our findings corroborate real-world clinical data generated from decades of studies suggesting a role for ATP levels in the regulation of RBC hemolytic propensity, especially extravascular hemolysis upon transfusion. 43 Similarly, it had been recently reported that hypoxanthine accumulation as a function of adenosine or AMP deaminase activation during storage is a marker of the metabolic storage lesion that predicts extravascular hemolysis in mice and humans.…”
Section: Discussionsupporting
confidence: 63%
“…Given their lack of de novo protein synthesis capacity, RBCs rely on dynamic metabolic reprogramming in response to environmental stimuli, including hypoxia or oxidant stress (e.g., at altitude or during exercise). 3 For example, small molecule metabolites such as ATP play critical roles in hemoglobin allostery by stabilizing the tense deoxygenated state and promoting oxygen release to tissues. 2 Relevant to biology at large, mitochondria-devoid RBCs represent a simplified model of eukaryotic cell metabolism, a cell type that exclusively relies on glycolysis as the main source of energy for the synthesis of ATP.…”
Section: Mainmentioning
confidence: 99%
See 3 more Smart Citations